2014
DOI: 10.4049/jimmunol.1303204
|View full text |Cite
|
Sign up to set email alerts
|

Fcγ Receptor Dependency of Agonistic CD40 Antibody in Lymphoma Therapy Can Be Overcome through Antibody Multimerization

Abstract: Immunomodulatory mAbs, led by the anti-CTLA4 mAb ipilimumab, are an exciting new class of drugs capable of promoting anticancer immunity and providing durable control of some tumors. Close analysis of a number of agents has revealed a critical yet variable role for Fcγ receptors in their efficacy. In this article, we reveal that agonistic anti-CD40 mAbs have an absolute requirement for cross-linking by inhibitory FcγRIIB when used systemically to treat established BCL1 syngeneic lymphoma, and therapy is lost w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 36 publications
2
56
1
Order By: Relevance
“…S3). This suggested that the agonist signaling capacity of these two antibodies is equivalent and is not dependent on FcgR binding, unlike anti-CD40 antibodies that require FcgR binding for their agonist activity (20). When administered in vivo, N297A-mutant mDTA-1 showed similar binding characteristics on intratumoral T cells and had equivalent pharmacokinetics properties as non-mutant mDTA-1 ( Supplementary Fig.…”
Section: Mdta-1 Preferentially Reduces Highly Activated Intratumoral mentioning
confidence: 71%
“…S3). This suggested that the agonist signaling capacity of these two antibodies is equivalent and is not dependent on FcgR binding, unlike anti-CD40 antibodies that require FcgR binding for their agonist activity (20). When administered in vivo, N297A-mutant mDTA-1 showed similar binding characteristics on intratumoral T cells and had equivalent pharmacokinetics properties as non-mutant mDTA-1 ( Supplementary Fig.…”
Section: Mdta-1 Preferentially Reduces Highly Activated Intratumoral mentioning
confidence: 71%
“…21 Work with CD40 has shown that simply cross-linking the receptors is sufficient for activity and that no downstream signaling is required. 20,23,30 Whether the same holds true for TGN1412 and CD28 remains to be confirmed.…”
Section: Discussionmentioning
confidence: 97%
“…For example, whereas the optimal immunestimulating, antitumor isotype for anti-CD40 mAb when injected i.v. is an mIgG1, due to its ability to bind avidly to mFcgRII and cross-link the associated CD40 molecules, a normally inert mIgG2a isotype is found to gain appreciable activity when introduced s.c., and this activity is dependent upon binding activatory mFcgR (13,15). Principally, this property is influenced by which FcgR are expressed in a given location and their affinity for a particular mAb isotype, but certainly comprehensive knowledge of FcgR expression patterns in each location will help in the finetuning and design of mAb reagents requiring FcgR engagement for specific functions.…”
Section: Discussionmentioning
confidence: 99%
“…As FDC are also a source of captured Ag, they may represent an ideal cell type for augmenting further Ag presentation and processing for subsequent T cell stimulation. This observation may therefore relate to the potent immune stimulating activity of mAb targeting TNF receptor super family members such as CD40 and DR4/5 (12)(13)(14)50). In contrast to direct targeting mAb such as rituximab, which are impaired by mFcgRII and hFcgRIIB, these receptors are now known to be an important component of immunomodulatory mAb activity, where they serve to further cross-link the target receptor for optimal signaling (20)(21)(22)(23)(24)(25)reviewed in Ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation